Identifikasi Permasalahan Mahasiswa FKIP Universitas Lampung Menggunakan Daftar Cek Masalah (DCM) - Mayasari, Shinta; Rahmayanthi, Ranni; Oktariana, Yohana; Kurniawati, Eka (Universitas Negeri Makassar, 2025)
This study was conducted to identify the most frequent problems faced by students of the Faculty of Teacher Training and Education (FKIP) at the University of Lampung, the differences in problems encountered based on study programs, and the most effective strategies to overcome these issues. The research employed a quantitative approach with a survey method. The study population consisted of all active undergraduate students from 19 study programs within FKIP. A total of 576 students were selected as research samples using a convenience sampling technique. The research instrument was the Problem Checklist (Daftar Cek Masalah/DCM), which reveals 11 domains of problems: health, economy, recreation and hobbies, social life, personal relationships, youth issues, family life, religion and morals, school adjustment, future and aspirations, and curriculum adjustment. The data were analyzed using descriptive statistics. The findings showed that health issues were the most frequently reported problem, identified in 16 study programs (84.2%). This was followed by social problems in 15 study programs (78.9%), and personal problems in 13 study programs (68.4%)